Associations of gestational diabetes mellitus with residential air pollution exposure in a large Southern California pregnancy cohort. (September 2019) - Jo, Heejoo; Eckel, Sandrah P.; Chen, Jiu-Chiuan; Cockburn, Myles; Martinez, Mayra P.; Chow, Ting; Lurmann, Fred; Funk, William E.; McConnell, Rob; Xiang, Anny H.
Abstract: Background: Studies of effects of air pollution on gestational diabetes mellitus (GDM) have not been consistent, and there has been little investigation of effects of exposure preceding pregnancy. In previous studies, the temporal relationship between exposure and GDM onset has been difficult to establish. Methods: Data were obtained for 239, 574 pregnancies between 1999 and 2009 in a population-based health care system with comprehensive electronic medical records. Concentrations of ambient nitrogen dioxide (NO2 ), particulate matter (PM) ≤2.5 μm in aerodynamic diameter (PM2.5 ) and ≤10 μm (PM10 ), and ozone (O3 ) during preconception and the first trimester of pregnancy at the residential birth address were estimated from regulatory air monitoring stations. Odds ratios (ORs) of GDM diagnosed in the second and third trimesters in association with pollutant exposure were estimated using generalized estimating equation models adjusted for birth year, medical center service areas, maternal age, race/ethnicity, education, census-tract household income, and parity. Results: In single-pollutant models, preconception NO2 was associated with increased risk of GDM (OR = 1.10 per 10.4 ppb, 95% confidence interval [CI]: 1.07, 1.13). First trimester NO2 was weakly associated with GDM, and this was not statistically significant (OR = 1.02 per 10.4 ppb, 95% CI: 0.99, 1.05). Preconception NO2 associations were robust in multi-pollutant models adjusted for first trimester NO2 with another co-pollutant from both exposure windows. In single-pollutant models, preconception PM2.5 and PM10 associations were associated with increased risk of GDM (OR = 1.04 per 6.5 μg/m 3, 95% CI: 1.01, 1.06; OR = 1.03 per 16.1 μg/m 3, 95% CI: 1.00, 1.06, respectively), but these effect estimates were not robust to adjustment for other pollutants. In single-pollutant models, preconception and first trimester O3 were associated with reduced risk of GDM (OR = 0.94 per 15.7 ppb, 95% CI: 0.92, 0.95; OR = 0.95 per 15.7 ppb, 95% CI: 0.94, 0.97), associations that were robust to adjustment for co-pollutants. Conclusions: Maternal exposure to NO2 during the preconception trimester may increase risk of GDM. Highlights: The date of GDM diagnosis was used to refine temporality with pollutant exposures. Independent associations of each pollutant and exposure window were assessed. Maternal exposure to NO2 during preconception was robustly associated with GDM.